Perancangan Tata Letak Gudang Sparepart Menggunakan Metode Dedicated Storage pada PT. Pelayaran Tonasa Lines - Della Ginza Ramadhan; A. Dian Sry Rezki Natsir; Andi Musdalifa Arini Sari (Jurnal Industri dan Teknologi Samawa, 2025)
Pelayaran Tonasa Lines is a company that distributes cement produced by PT. Semen Tonasa to various cities across Indonesia by ship. However, the company often faces challenges in its ship operations due to delays in supplying parts needed for ship maintenance, which disrupts the distribution process. This issue arises from an unorganized spare parts warehouse management system, with parts stored using a randomized storage method, where placement is irregular and not fixed. Consequently, spare parts retrieval takes longer, especially when warehouse staff changes. To address this problem, a study was conducted to redesign the warehouse layout and storage system using the dedicated storage method, assigning each spare part a fixed storage location. The study results indicate a significant improvement in efficiency, with a reduction in round-trip travel distance by 340 meters from an initial 988 meters (a 65.6% decrease), a reduction in occupied floor area by 9.5 square meters from an initial 39.5 square meters (a 75.9% decrease), and an average rack travel distance reduction of 17.9 meters from 44.9 meters (a 60.1% decrease). These findings demonstrate that the implementation of dedicated storage provides substantial improvements in spare parts warehouse management at PT. Pelayaran Tonasa Lines.